Pelatihan Penyusunan Laporan Keuangan Menggunakan Aplikasi Catatan Keuangan Pada Usaha UMKM Pabrik Tahu TS - Fitriano, Yun; Nainggolan, Sulastri; Madewi.KH, Wista Elis; Hutabarat, Suzeti Monica (Jurnal Dehasen Mengabdi, 2022)
Financial reports are very important for MSME actors. Every MSME actor is required to be able to make financial reports so that they can monitor how their business develops from time to time. There are several obstacles that make MSMEs unable to access applications in compiling financial reports, such as their ignorance that there is a Financial Records application as more of a solution to assist them in compiling financial reports and how to use the application. The TS tofu factory is one of the MSME businesses in Bengkulu City, but the TS tofu factory has never known or even understood the use of the Financial Records application. Therefore, as a Dehasen University service team, we provide training in using the Financial Records application to record the results of sales reports, expense reports and business profits as well as accounts payable and accounts receivable reports at the TS tofu factory. The method used in the three stages of this service is the interview method by asking questions to gather information and collect data and the direct practice method of recording financial statements starting from recording sales and expenditure transactions to accounts payable and accounts receivable and followed by posting financial reports via Microsoft Excel, PDF or CSV.